Development of Heat and Temperature E-Module Containing Local Wisdom in South Kalimantan - Muhammad Akhsan Arif; Siti Jubaidah; Lutfiyanti Fitriah; Fahmi Yahya (Universitas Lambung Mangkurat, 2023)
The aim of this study was to produce a valid electronic module integrated the local wisdom in South Kalimantan on heat and temperature materials, receiving positive responses from students. The ADDIE model was employed for this study, focusing on high school students in South Kalimantan, totaling 62 participants. Research instruments included validation sheets and response questionnaires, with data collected through a survey technique. Data analysis involved the Aiken formula and mean calculations. Results indicated high validity for the e-module concerning both media and material aspects (0.92-1.00). Students' average response to the e-module was excellent, scoring 4.41. Consequently, the e-module demonstrated validity and positive reception among students, making it suitable for use in physics education, particularly for heat and temperature topics.